2021
DOI: 10.1038/s41598-021-91733-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of functional properties of nano $$\hbox {TiO}_2$$ coated cotton composites by artificial neural network

Abstract: This paper represents the efficiency of machine learning tool, i.e., artificial neural network (ANN), for the prediction of functional properties of nano titanium dioxide coated cotton composites. A comparative analysis was performed between the predicted results of ANN, multiple linear regression (MLR) and experimental results. ANN was applied to map out the complex input-output conditions to predict the optimal results. A backpropagation ANN model called a multilayer perceptron (MLP), trained with Bayesian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Linear regression is one of the basic tools in statistics to correlate between different variables for a set of observations. Applications of linear regression can vary from simple tasks, such as simple line fitting, to a much more complex task, such as classification and pattern recognition [ 31 , 32 , 33 ]. To increase the model possibility for higher prediction probabilities, another column was added to the input data of the model, using the combined linear regression and ML method by constructing the “|𝑚 × 𝑏|” term for each material where “m” and “b” are the linear regression variables, in other words, applying linear regression separately to each of the material results.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression is one of the basic tools in statistics to correlate between different variables for a set of observations. Applications of linear regression can vary from simple tasks, such as simple line fitting, to a much more complex task, such as classification and pattern recognition [ 31 , 32 , 33 ]. To increase the model possibility for higher prediction probabilities, another column was added to the input data of the model, using the combined linear regression and ML method by constructing the “|𝑚 × 𝑏|” term for each material where “m” and “b” are the linear regression variables, in other words, applying linear regression separately to each of the material results.…”
Section: Methodsmentioning
confidence: 99%
“…The use of machine learning in textiles, especially for classification, has shown its potential exponentially in the current era [ 13 , 14 ]. Zimmerling et al reported the application of Gaussian regression algorithm to improve the geometrical shapes of fiber reinforced textile composites.…”
Section: Introductionmentioning
confidence: 99%
“…Here, in this current study, an attempt has been made to develop a prediction model by using machine learning tools that can work in two ways i.e., correlates the actual response of coated fabric with process variables, analyse the predicted response of DE and indicate which approach is better as a prediction model in reality. Nowadays, artificial neural network (ANN) exhibits a strong advantage in capturing any type of existing relationship from given data as it does not include a physical mechanism and a mathematical model 14 . Thanks to the training process, ANN can learn, understand and recognize the information treatment rules, adapt and predict the wanted output variables from database considered as input variables 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%